Is there a relationship between anthropic action on the environment and the Deadline according to Chico Xavier? - Gorne, Íris Batista; Romualdo, Sanderson dos Santos; Rocha, Cézar Henrique Barra (Electronic Journal "Fórum Ambiental da Alta Paulista", 2022)
The discussion about the existence of a spiritual plane and the possibility of communication between this plane and human beings permeates for decades, from which many questions arise, with the difficulty of proof by scientific means being the main obstacle. In this context, the authors intended to relate Spiritualist messages, such as the Deadline according to the medium Chico Xavier, as tools that are not only helpful in understanding, but are also part of science in actions to mitigate the environmental impacts caused by anthropic action. Therefore, this purpose was developed from a literature review, consulting the main academic research bases and reference books about Spiritism, in addition to the experience of the authors. It is suggested that the Covid-19 pandemic is the Deadline described by Chico Xavier, thus representing the most severe threat to global health in this century. The prophecy highlighted the various Spiritist communities with regard to the directions of Planet Earth associated with the current economic production model. Disordered consumption and exploration of natural resources have generated social, economic and environmental consequences that are being seen by the planet and that are related to the Spiritist practices with regard to the search for social equality in all its aspects. Therefore, the deceleration of industrial production, which leads to the enrichment of the few at the expense of the greater part of society, and the use of renewable environmental resources, as well as the protection of all biodiversity, must be encouraged. There is also an urgent need to consider Spiritism as a pillar for the development of science.